Improving Collaboration Abilities and Students’ Learning Outcomes Through Presentation Based Cooperative - arif djunaidi (Department of Mathematics Education University of Muhammadiyah Malang, 2021)
Students need to be optimally facilitated in expressing ideas and ideas in their minds through collaborative activities in the learning process. The purpose of this study was to explore the improvement of collaboration skills and student learning outcomes through presentation-based cooperative learning in the mathematics learning strategy subject. The research approach is qualitative and a type of classroom action research. The subjects in the study were 37 students who took the mathematics learning strategy course. Data collection was carried out through observation, tests, and field notes. The results showed that the collaborative abilities of students from the first cycle to the second cycle increased. The ability to interact effectively with fellow students, the ability to guide and lead peers, work effectively in groups, and the ability to manage tasks systematically increased, but the ability to be responsible did not show any improvement. The completeness of student learning outcomes at a predetermined minimum completeness score of 75 has increased, 76% of students complete in the first cycle and 84% of students complete in the second cycle.